The Effect Of Library Facilities On Library Satisfaction At State Islamic University of North Sumatera Library - Abdi Mubarak Syam (International Journal of Cultural and Social Science, 2022)
Library facilities are all types of equipment, work equipment and other service facilities that function as the main / auxiliary tool in carrying out work or everything that is used, used, occupied and enjoyed by users. User satisfaction is a condition where the desires, expectations and needs of customers are met. A service is considered satisfactory if the service can meet the needs and expectations of customers. The purpose of this study was to determine whether or not the influence of library facilities on user satisfaction at the library of UIN North Sumatra Medan. This research approach uses quantitative. Data collection techniques using observation techniques and questionnaires. The data analysis technique used simple linear regression analysis with the help of SPSS version 22 software. The results of this study indicate that there is an influence of library facilities on user satisfaction at the UIN North Sumatra Medan Library.